Expression of Mineralized Tissue Associated Proteins: Dentin Sialoprotein and Phosphophoryn in Rodent Hair Follicles - Tang, Xu-na (2011)
BACKGROUND: Mammalian hair development and tooth development are controlled by a series of reciprocal epithelial-mesenchymal interactions. Similar growth factors and transcription factors, such as fibroblast growth factor (FGF), sonic hedgehog homolog (SHH), bone morphogenetic proteins (BMPs) and Wnt10a, were reported to be involved in both of these interactions. Dentin sialoprotein (DSP) and phosphophoryn (PP) are the two major non-collagenous proteins secreted by odontoblasts that participate in dentin mineralization during tooth development. Because of striking similarities between tooth development and hair follicle development, we investigated whether DSP and/or PP proteins may also play a role in hair follicle development. OBJECTIVE: In this study, we examined the presence and location of DSP/PP proteins during hair follicle development. METHODS: Rat PP proteins were detected using immunohistochemical/immunofluorescent staining. DSP-PP mRNAs were detected by in situ hybridization with riboprobes. LacZ expression was detected in mouse tissues using a DSP-PP promoter-driven LUC in transgenic mice. RESULTS: We found that PP proteins and DSP-PP mRNAs are present in rat hair follicles. We also demonstrate that an 8 kb DSP-PP promoter is able to drive lacZ expression in hair follicles. CONCLUSION: We have firmly established the presence of DSP/PP in mouse and rat hair follicles by immunohistochemical/immunofluorescent staining, in situ hybridization with riboprobes and transgenic mice studies. The expression of DSP/PP in hair follicles is the first demonstration that major mineralization proteins likely may also contribute to soft tissue development. This finding opens a new avenue for future investigations into the molecular-genetic management of soft tissue development.